Maternal smoking during pregnancy and early development of overweight and growth deficit in children: an analysis of survival - Poliana Cristina de Almeida Fonseca; Carolina Abreu de Carvalho; Vitória Abreu de Carvalho; Andréia Queiroz Ribeiro; Silvia Eloiza Priore; Sylvia do Carmo Castro Franceschini; Sarah Aparecida Vieira
Abstract Objectives: to evaluate the association between smoking during pregnancy and nutritional status. Methods: cohort study with a sample of 460 children in the baseline. The children were assessed four times, being measured for weight and length to be converted in indexes length forage (L/A) and body mass index forage (BMI/A) in Z-score. The time until occurrence of growth deficit and overweight was calculated in days and compared to maternal smoking during pregnancy. To assess the association between smoking during pregnancy and the outcomes, a Hazard Ratio by Cox regression was obtained, adjusting by confounding variables selected from Directed Acyclic Graphs (DAG). Results: the time until occurrence of growth deficit and overweight was lower in children whose mothers smoked during pregnancy. Smoking during pregnancy was a risk factor for length deficit (HR = 2.84; CI95% = 1.42 to 5.70) and for overweight (HR = 1.96; CI95% = 1, 09 to 3.53), even after the adjustment. Conclusions: maternal smoking was a changeable factor associated with anthropometric outcomes, which demonstrates the need for actions to combat smoking during pregnancy in order to prevent early nutritional deviations.